Material saving and cost reduction with hot forming of U‐shaped titanium part. Issue 9 (9th September 2014) - Stutz, L.; Beck, W.; Arends, S.; Horstmann, M.; Ventzke, Volker; Kashaev, N.
<x xml:space="preserve">Abstract</x> Titanium alloy sheets are widely used for highly loaded components in the aerospace industry as well as spacecrafts. The unique combination of high strength, outstanding corrosion resistance and thermal endurance makes titanium alloys the preferred material for applications with severe requirements. Due to the limited formability at room temperature, forming processes have to be conducted in a multitude of steps what is costly and labour intensive. Additionally, typical titanium alloy sheets show a significant anisotropy of mechanical properties and material flow. Undesired earing, wall thickness variation and residual stresses are the result. Complex shaped parts can be produced at elevated temperatures to avoid named drawbacks. The present work introduces a newly developed hot deep drawing process, applied to titanium sheets at FormTech. In comparison with conventional superplastic forming processes via gas pressure, hot deep drawing comes with a significantly reduced process time and hence, increased output over time. Titanium sheets of the work horse alloy Ti–6Al–4V were formed in a single stroke to a U‐shaped component at process temperatures ranging from 750 to 890 °C. Specimens were extracted to validate the neglectable influence of the hot forming process on mechanical properties and fatigue behaviour. In conclusion, hot deep drawing of titanium sheets offers a cost efficient alternative to a gas pressure superplastic forming process, while maintaining its main benefits such as significantly improved formability, low residual stresses and tight tolerances.